RANCANG BANGUN SISTEM PENAMPUNGAN AIR MENGGUNAKAN TANDON ATAS SECARA OTOMATIS BERBASIS MIKROKONTROLER - Setyawan, Rezky; Amrita, Anak Agung Ngurah; Oka Saputra, Komang (Jurnal SPEKTRUM, 2021)
Water reservoirs are temporary water reservoirs, usually placed at the highest. The community places or installs water reservoirs above the house by using gravity so that the water can run down swiftly. In general, to get clean water, people use PDAM services or use well water. Generally, in urban areas, the water sources used to supply water reservoirs come from PDAMs or wells (boreholes). In the clean water storage system using an upper reservoir has several problems, such as monitoring the available water capacity in the borehole which cannot be known so that the pump will operate for a long time to fill water and cause damage to the pump, due to the difficulty of monitoring and controlling. The condition of the upper reservoir water storage is therefore designed in this study with a prototype "WATER SANDING SYSTEM USING UP TANDON AUTOMATICALLY BASED ON MICROCONTROLLER" which can be monitored via SMS and manually.